PENGARUH PENILAIAN PRESTASI KERJA DAN KOMUNIKASI ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN (Studi Kasus Karyawan Bagian Sekretariat Perusahaan PT. Perkebunan Nusantara V Pekanbaru) - Yuni Triana; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effect of performance appraisal and organizational communication on employee job satisfaction partially and simultaneously.  This study uses a questionnaire as a data collection tool that is distributed to 86 respondents to the employees of the company secretary of PT.  Perkebunan Nusantara V Pekanbaru.  The data is then processed using descriptive analysis and statistical analysis using SPSS 21.0 by conducting validity, reliability, determination (R2), simple linear analysis, multiple linear regression analysis and hypothesis testing with t (partial) and F (simultaneous) tests.The results showed that the first hypothesis testing is the assessment of work performance on employee job satisfaction that is tCalculate (6,158) > tTable (1,990), meaning that the assessment of work performance has a significant effect on employee job satisfaction.  The second organizational communication is tCalculate (6,143) > tTable (1,990), meaning that communication has a significant effect on employee job satisfaction.  Test results Fcalculate (23.266) > Ftable (3.11), meaning that the assessment of work performance and organizational communication simultaneously has a significant effect on employee job satisfaction. Keywords: Job Performance Evaluation Assessment, Organizational Communication, Employee Job Satisfaction.